Characterization of CME-driven shock in the interplanetary medium using type II radio bursts (2017)
Type II radio bursts are indirect signatures of the fast magnetosonic shock formation in the heliosphere. Those types of MHD shocks accelerate electron beams that via plasma emission mechanism produce electromagnetic radiation. In particular, fast Coronal Mass Ejections (CMEs) produces CME-driven shocks that can be tracked using this radio emission. Observation indicates that type II burst is intermittent in time, indicating that the shock formation and observation are highly dependent on the physical condition of the propagation environment. Using multi-spacecraft observations from STEREO, Wind and SOHO missions, we study the formation and main properties of CME-drive shock since it initial stages to reach 1AU. We present a database of 27 events of Type II radio burst, including features of the flare and CME associated, radio emission and IP shock features. Four events of the sample exhibit Type II radio burst signatures observed in-situ. For them, we study the electrostatic wave activity in-situ in order to determine Langmuir wave existence and the radio emission source region in the interplanetary shock vicinity. For August 18, 2010 event, we examine the structure, propagation, and morphology of the CME-driven shock using multi-observable sources. We describe the main features of the associated eruptive events: flare and CME, the solar burst associated and the interplanetary shock and magnetic cloud detected in-situ. We determine the most probable physical scenario for the generation of radio emission using empirical electron density models. From the 4 events studied, only two present evidence of radio emission source region and one of them shows Langmuir wave activity in the downstream region. The results for August 18, 2010 event indicates that the complex Type II radio burst is observed at high and low frequencies, both related to a CME-driven shock. We suggest that a CME-CME interaction could originate the complex radio emission observed at high frequencies at the initial stages of the event. For the case of slow-drifting low-frequency type II radio emission, we suggest that this may be related to CIR-CME dynamics close to STEREO-A which detects the interplanetary shock in-situ.